Blockchain based trusted traceability system scheme for raw milk supply chain - Ying LIU; Hongbo FAN; Shouqun MA; Zhiwei GAO; Jinjiang LIU (Dianxin kexue)
Abtract: The development of raw milk is an important direction for the development of China’s dairy industry, and a traceability system for the raw milk industry was proposed for the development of the entire industry crucially.The characteristics of the raw milk industry were analyzed and four major problems were proposed as the timeliness, the problems found after the fact, the difficulty in tracing the victims, the quality control system, such as difficulties in gaining trust, which were the main characteristics that distinguish the raw milk industry from other agricultural industries, and leaded to traceability in traditional agriculture.The mechanism or even the popular blockchain-based traceability mechanism for agricultural products could not meet the traceability requirements of the raw milk industry.Based on this finding, RMChain, a traceability system for raw milk supply chain system scheme, was designed to meet the requirements of the existing blockchain-based traceability mechanisms in the raw milk industry.In addition to the various advantages of the chain traceability mechanism, it was also optimized specifically for the characteristics of raw milk, which made it easy for users to trace the product and facilitate the traceability of the milk.The tracking and location of problem milk and consumer compensation effectively improved the traceability status of the fresh milk industry.For the problem of large files seriously affecting the performance of the blockchain, a multi-party storage model based on the importance of data was also designed.The feasibility of RMChain was verified.